2010
DOI: 10.1264/jsme2.me09172
|View full text |Cite
|
Sign up to set email alerts
|

Factors Controlling Long-Term Survival and Growth of Naturalized Escherichia coli Populations in Temperate Field Soils

Abstract: While Escherichia coli is widely used as an indicator of fecal contamination of waterways, recent studies suggest that this bacterium may become "naturalized" to soils. In this study, we investigated the survival and growth of naturalized E. coli in temperate soil in northern Minnesota. A spontaneously-occurring, antibiotic resistant E. coli strain, KS7-NR, was added to a field site at 10 3 cells (g soil) −1 . The survival and growth of E. coli KS7-NR were followed from June to October, by using colony counts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 29 publications
3
55
0
Order By: Relevance
“…1C). On 23 May 2011, three exclosure boxes (referred to as KS14I), made from 32-gallon trash cans (50-cm diameter) as described previously (34), were buried at the KS14 location in order to exclude external enterococcal sources: runoff and feces deposition from animals. Four mesh-covered windows were placed into the exclosure boxes to facilitate air exchange.…”
Section: Methodsmentioning
confidence: 99%
“…1C). On 23 May 2011, three exclosure boxes (referred to as KS14I), made from 32-gallon trash cans (50-cm diameter) as described previously (34), were buried at the KS14 location in order to exclude external enterococcal sources: runoff and feces deposition from animals. Four mesh-covered windows were placed into the exclosure boxes to facilitate air exchange.…”
Section: Methodsmentioning
confidence: 99%
“…When sand was amended with plankton in laboratory experiments, E. coli initially increased about 2 log and then gradually decreased, but remained 1 log higher than initial concentrations (Byappanahalli et al 2006b). Generally, more complex carbon sources prolonged the replication of E. coli in microcosms relative to rapidly metabolizable substrates such as lactose (Ishii et al 2010). Another study reported that survival of E. coli and enterococci in microcosms was greater when wrack (macroalgae that has washed onto the shore) was applied to the surface of the sand (Imamura et al 2011).…”
Section: Fate Ecology and Population Biology/geneticsmentioning
confidence: 99%
“…Further, faster growth of environmental than laboratory strains has been reported by Brennan et al (2010a). Recent research has shown that E. coli strains can become residents in many different types of soils, in both temperate and tropical environments (Brennan et al, 2010a;Brennan et al, 2010b;Goto and Yan, 2011;Ishii et al, 2006;Ishii et al, 2010;Nautiyal et al, 2010). Brennan et al (2010b), for example, reported that E. coli had persisted in temperate maritime soils for more than nine years.…”
Section: Attenuation In the Form Of Predation Retention And Releasementioning
confidence: 95%